Troponins can it determine the outcome in acute organophosphorus poisoning? - Shivaraj, Kiran; Shettigar, Shruti K. (International Journal of Research in Medical Sciences, 2019)
Background: India has shown a sharp rise in the number of suicidal poisoning in the past few years and organo-phosphorus compounds are the most commonly implicated. This is a prospective study done to assess if troponins can be used as a prognostic marker in patients with organophosphate poisoning. Methods: Author conducted a prospective study on 50 patients to measure the level of troponin T and CK-MB on admission and Day 3 in patients with OP poisoning. This was then correlated to the severity of poisoning and also studied for its association with outcomes like respiratory failure or death. The primary endpoints were death and respiratory failure while secondary endpoint was the length of ICU stay. Results: With 0.1 ng/ml taken as the cut off for Troponin- T, and 40 U/L for CK-MB, positive cardiac enzymes were seen only in 10% of the patients, but all the patients in this group developed res-piratory failure. The mean Troponin T and CK-MB levels (0.1142±0.06 ng/ml and 39.14±8.23 U/L) were higher for patients who died when compared to the survivors. A similar picture was seen in patients with respiratory failure (Troponin T 0.0895±0.01 ng/ml and 34.65±11.66 U/L) as compared to those without respiratory failure. Conclusions: The level of cardiac enzymes correlated well with the severity of poisoning, days of ICU stay and outcome, thus suggesting its use as a prognostic indicator of organophosphorus poisoning.